Assembly of tetra-nuclear YbIII-containing selenotungstate clusters: synthesis, structures, and magnetic properties. Issue 33 (5th August 2021) - Han, Li-Zhi; Jiao, Cheng-Qi; Chen, Wei-Chao; Shao, Kui-Zhan; Jin, Long-Yi; Su, Zhong-Min
Abstract : The first Yb III -containing POMs with a selenium heteroatom have been isolated, namely Keggin Yb4 Se6 W44 and Wells–Dawson Yb4 Se6 W45 , the former of which exhibits field-induced SMM behavior. Abstract : Two tetra-nuclear Yb III -incorporated selenotungstate clusters, Keggin (C2 H8 N)6 Na14 [Yb4 Se6 W44 O160 (H2 O)12 ]·40H2 O (1 ) and Wells–Dawson (C2 H8 N)4 Na14 [Yb4 Se6 W45 O159 (OH)6 (H2 O)11 ]·38H2 O (2 ), have been isolated through a pH-controlled assembly, which exhibit the first Yb III -containing polyoxotungstates with selenium heteroatoms. Their assemblies rely on the structure-directing effects of SeO3 2− anion templates to give rise to available Se-containing Keggin-/Wells–Dawson-type motifs. Both compounds were characterized by single-crystal X-ray diffraction, IR spectroscopy, power X-ray diffraction (XRD), thermogravimetric analysis (TGA), X-ray photoelectron spectroscopy (XPS) as well as electrospray ionization mass spectrometry (ESI-MS). Furthermore, systematic magnetic studies revealed that 1 exhibits field-induced single-molecule magnetic behavior with a pre-exponential factor of τ 0 = 6.60(7) × 10 −8 s and a relaxation energy barrier of Δ E / k B = 39.44(2) K, while 2 only displays antiferromagnetic interactions between the ytterbium centers.